Political Communication of the Incumbent Village Head in the Pilkades of Sungai Sebesi, Kundur District, Karimun Regency in 2022 - Abidin, Muhammad Zainal; Afrizal, Afrizal; Darmawan, Eki (Formosa Journal of Applied Sciences, 2024)
Village head elections are an exercise of popular sovereignty. success requires political communication in the pilkades. Nazaruddin is an incumbent village head who served for three consecutive terms in the Sungai Sebesi village head election. This phenomenon indicates success in maintaining power by using political communication. The purpose of this research is to see how the political communication of the incumbent village head in winning the pilkades. The research method used in this research is qualitative method. The results of this study indicate that in maintaining stature and strengthening institutions Nazaruddin always maintains a good personality and improves his performance for the advancement of village development. creating togetherness he shows by uniting common goals to advance the village even better in the future. building consensus Nazaruddin always prioritizes common interests, and always opens himself in every decision making.